Does Corruption Threaten Foreign Investment? : A Case Study of ASEAN-1 - Liasulistia Ningsih; Indra Ismayudi Tanjung (Universitas KH. Abdul Chalim Mojokerto, 2026)
Foreign Direct Investment (FDI) is one of the important factors used by various countries to stimulate economic growth, as FDI provides capital for the host economy and promotes technology transfer. In addition to understanding the factors that encourage FDI inflows, identifying the factors that hinder FDI inflows in a country is equally important. Therefore, this study aims to empirically examine the role of corruption in the presence of FDI. Based on several previous studies, there are still differences in findings regarding how corruption affects FDI. Thus, this analysis specifically examines whether corruption harms or instead encourages the level of FDI in a country. This study uses secondary data from Transparency International (Corruption Perceptions Index) and the World Bank. The analysis period used in this study is from 2012 to 2024, applying a static panel method to determine the effect of corruption on FDI in 9 countries that are members of ASEAN. The results show that corruption has a significant effect on FDI, where the higher the Corruption Perceptions Index of a country, the higher the level of FDI.